Wind Field Synthesis for Animating Wind-induced Vibration - Khorloo, Oyundolgor; Gunjee, Zorig; Sosorbaram, Batjargal; Chiba, Norishige (International Journal of Virtual Reality, 2011)
We present a simple method to generate three-dimensional frozen and non-frozen turbulent wind fields for use in the animation of wind-induced motion. Our approach uses 1/f^_ noise to match the characteristics of natural wind. By employing a noise-based approach, the complexity as well as computational cost is reduced. Additionally, by considering key characteristics of actual wind that are applied in the structural engineering field, our proposed method is able to produce plausible results in outdoor wind field simulations. In this paper, we describe the implementation results of our proposed method and compare them with other existing approaches used to construct turbulent wind fields. The implementation and visualization are carried out for both two- and three-dimensional scenarios and compared with the results of other well-known methods.